2005
DOI: 10.1242/jcs.02448
|View full text |Cite
|
Sign up to set email alerts
|

Roles of heterogeneous nuclear ribonucleoproteins A and B in cell proliferation

Abstract: IntroductionHeterogeneous nuclear ribonucleoprotein particle proteins (hnRNPs) are abundant, multi-tasking proteins that play a central role in RNA metabolism. They are involved in packaging nascent hnRNA, alternative RNA splicing, mRNA export from the nucleus, and cytoplasmic trafficking, stability and translation (Dreyfuss et al., 2002;Krecic and Swanson, 1999;Shyu and Wilkinson, 2000;Weighardt et al., 1996). They also have an as yet poorly defined role in telomere maintenance.More than 20 hnRNPs, many of wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
115
1
3

Year Published

2009
2009
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(133 citation statements)
references
References 55 publications
14
115
1
3
Order By: Relevance
“…hnRNPA2/B1 has been reported as a gene transcriptional activator or repressor in different gene regulations. For example, hnRNPA2 transcriptionally represses expression of vitamin D receptor, but it works more like an activator for Brca1 gene transcription (14,38). In this study, our current findings also revealed that hnRNPA2/B1 is an activator that regulates SMC Sm␣a and Sm22 gene expression during SMC differentiation from ES cells.…”
Section: Hnrnpa2/b1 Promote Smooth Muscle Differentiationsupporting
confidence: 71%
“…hnRNPA2/B1 has been reported as a gene transcriptional activator or repressor in different gene regulations. For example, hnRNPA2 transcriptionally represses expression of vitamin D receptor, but it works more like an activator for Brca1 gene transcription (14,38). In this study, our current findings also revealed that hnRNPA2/B1 is an activator that regulates SMC Sm␣a and Sm22 gene expression during SMC differentiation from ES cells.…”
Section: Hnrnpa2/b1 Promote Smooth Muscle Differentiationsupporting
confidence: 71%
“…For one, it was found to have a protective effect against apoptosis, possibly in part through an effect on AS of caspase-2 pre-mRNA (Jiang et al 1998). In addition, depletion of hnRNP A/B proteins in Colo16 cells resulted in reduced proliferation, with hnRNP A2 playing a particularly important role (Jiang et al 1998;He et al 2005). Consistent with an important role in tumors, siRNA-mediated knockdown of hnRNP A1/A2 in cancer cells, but not normal cells, can result in apoptosis (Patry et al 2003).…”
Section: Hnrnp and Sr Proteins In Proliferation And Cancermentioning
confidence: 99%
“…Suppression of hnRNPA2 increases p21 (He et al, 2005), while downregulation of hnRNPK and p21 switches between apoptosis and growth arrest induced by p53 (Enge et al, 2009). Hence, the multi-hnRNP-regulated ANXA7 could interfere with p53 cell survival pathways in p53/PTEN-null PC3.…”
Section: Discussionmentioning
confidence: 99%